Synthesis of Gold Nanoparticles Using Ascorbic Acid as a Bioreductor and the Effect of Uric Acid - Rachmawati, Yulle; Taufikurohmah, Titik (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Gold nanoparticles (AuNPs), ranging in size from 1 to 100 nm, represent one of the most significant advancements in metal-based technologies in recent years. Their application in the medical field, especially as drug delivery agents, is particularly noteworthy and demonstrates their transformative potential. This study aims to synthesize AuNPs using HAuCl4 as a precursor and ascorbic acid as a bioreductant at a concentration of 20 ppm with a bottom-up method. The result of the synthesis process yields a striking burgundy-colored solution, signifying the successful formation of gold nanoparticles. The results of UV-Vis characterization provided insightful data on the transformation of the HAuCl4 solution. Initially recorded at a wavelength of 314.60 nm, the solution underwent a notable shift to 523.50 nm after the synthesis process, demonstrating an absorbance value of 0.323. Furthermore, the transmission electron microscopy (TEM) analysis illuminated the unique characteristics of the synthesized nanoparticles, revealing an average particle size of 6.23 nm with the highest particle frequency in the range of 6-8 nm. Moreover, the result of clinical trials conducted with ten randomly selected volunteers, who received 20 ppm of AuNPs over a five-week period, demonstrated that seven out of ten participants experienced a significant reduction in uric acid levels, underscoring the therapeutic potential of gold nanoparticles. Microscopic observations following the injection revealed that volunteers with normal uric acid levels exhibited fewer leukocytes than those with elevated uric acid levels, who were noted to have leukocyte counts up to three times higher. In conclusion, the synthesis of AuNPs using ascorbic acid is marked by a wine-red solution and a significant absorption wavelength shift to the 500–600 nm range. The positive results of the clinical trial reflect the ability of AuNPs to lower uric acid levels, thereby paving the way for innovative nanotechnology-based therapeutic strategies in the medical field.